2006
DOI: 10.1007/s11258-006-9127-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in leaf area index and stand leaf mass of European beech across gradients of soil acidity and precipitation

Abstract: Leaf area index (LAI, the one-sided foliage area per unit ground surface area) is a key determinant of plant productivity which has a large influence on water and energy exchange between vegetation and the atmosphere. The variation in forest LAI across landscapes and environmental gradients and its causes are not sufficiently understood. We measured the LAI of European beech (Fagus sylvatica) by litter trapping in 23 closed, mature stands across gradients of rainfall and soil acidity or fertility. With a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
10
55
3
1
Order By: Relevance
“…Moreover, the use of ecological variables in our analyses allowed an objective and broadly comparable evaluation of the influence of the applied management options. The selected variables and experimental designs used were in accordance with that of other studies specifically addressing beech forest dynamics (e.g., Chianucci and Cutini 2013;Genet et al 2010;Lebourgeois et al 2005;Leuschner et al 2006;Meier and Leuschner 2008). Based on comparisons with these reports, we conclude that our studied stands are characterized by medium-high productivity, as revealed by the average values of canopy attributes.…”
Section: Resultssupporting
confidence: 71%
“…Moreover, the use of ecological variables in our analyses allowed an objective and broadly comparable evaluation of the influence of the applied management options. The selected variables and experimental designs used were in accordance with that of other studies specifically addressing beech forest dynamics (e.g., Chianucci and Cutini 2013;Genet et al 2010;Lebourgeois et al 2005;Leuschner et al 2006;Meier and Leuschner 2008). Based on comparisons with these reports, we conclude that our studied stands are characterized by medium-high productivity, as revealed by the average values of canopy attributes.…”
Section: Resultssupporting
confidence: 71%
“…Maass et al (1995) reported that LAI may also change within ecosystems depending on the site conditions, especially soil fertility, nutrients, and water supply. On the other hand, other authors have investigated the LAI in different forest ecosystems, reporting values varying from 1.7 to 5.3 m 2 m -2 in a coniferous forest (Pierce & Running 1988), from 0.5 to 8 m 2 m -2 in temperate deciduous forests (Le Dantec et al 2000) and from 5.6 to 9.5 m 2 m -2 in European beech stands (Leuschner et al 2006). The latter values are greater than the LAI values obtained in the current study.…”
Section: Leaf Area Index Light Transmission and Gapcontrasting
confidence: 81%
“…The latter values are greater than the LAI values obtained in the current study. According to previous studies (Breda & Granier 1996, Leuschner et al 2006), these differences could be due to the type and age of the stand and the availability of water in the soil, which is determined by climate and the properties of the soil as well as the different methods used.…”
Section: Leaf Area Index Light Transmission and Gapmentioning
confidence: 99%
“…However, this result is not generalizable as the studied hardwood and softwood species were species of different shade tolerances (Valladares and Niinemets, 2008) with the hardwood species being the most shade-tolerant species. In addition, Individuals of the two studied softwood species grow at higher elevations and in colder sites than those of the two studied hardwood species, with consequences both on allometries and on leaf area density (López-Serrano et al, 2005;Astrup and Larson, 2006;Leuschner et al, 2006;Lefrançois et al, 2008).…”
Section: Tree Light Capture and Overstory Heterogeneitymentioning
confidence: 94%